A Feasibility Study of a Leader-Follower Multi-Robot Formation for TDLAS Assisted Methane Detection in Open Spaces. - González-Monroy, Javier; Ojeda Morala, José; González-Jiménez, Antonio Javier (My University, 2023)
This work deals with the problem of detecting and localizing methane emission sources in open spaces with a mobile robot equipped with a remote gas detector (TDLAS). To reduce the long inspection time of traditional approaches which use the ground as the natural reflector, in this work, we analyze the feasibility of a leader-follower formation, where one robot, the leader, carries the remote gas detector that scans horizontally, parallel to the ground, and a second robot, the follower, that acts as an artificial reflector. We present a visual tracking mechanism for the relative pose estimation of both mobile platforms to extend the measurement range up to 10 m. Results in a 70 m2 experimental area demonstrate that this approach is effective for a fast location of methane gas sources.
Keywords: Metano; Detectores de gases; Robots autónomos; Gases - Análisis; Methane; TDLAS; Robotics